The use of cluster sampling to determine aid needs in Gorzny, Chechnya in 1995 - Drysdale, Sean, et al. (2000)
War broke out in Chechnya in November 1994 following a three-year economic blockade. It caused widespread destruction in the capital Grozny. In April 1995 Medical Relief International - or Merlin, a British medical non-governmental organisation (NGO) - began a programme to provide medical supplies, support health centres, control communicable disease and promote preventive health-care in Grozny. In July 1995 the agency undertook a city-wide needs assessment using a modification of the cluster sampling technique developed by the Expanded Programme on Immunisation. This showed that most people had enough drinking-water, food and fuel but that provision of medical care was inadequate. The survey allowed Merlin to redirect resources earmarked for a clean water programme towards health education and improving primary health-care services. It also showed that rapid assessment by a statistically satisfactory method is both possible and useful in such a situation. - Reproduced
Keywords: Medicare; Poor - Medical care - Chechnya; Medical aid - Chechnya; Health services